Polygamy Law Reform Through the Development of the Aceh Qanun: A New Approach to Protecting the Rights of Women and Children in Indonesia - Pelu, Ibnu Elmi AS; Tarantang, Jefry; Fauzi, Ahmad; Badarulzaman, Muhammad Hafiz; Sururie, Ramdani Wahyu; Anwar, Syahrul (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
Aiming to legalize the practice of polygamy through the Raqan regulation, which is then outlined in the family Qanun, it needs to have restrictions on practicing polygamy, such as the concept of justice and sanctions for abuse committed by a husband. The purpose is to protect women as human beings whose rights must be protected along with the obligations and be executed. Then, the research aimed to analyze the construction of Islamic law reform in the family sector, especially in protecting the position of women and children in the context of the structure of the legal order and the occurrence of polygamy without the permission of the Mahkamah Syar’iyah in Nanggroe Aceh Darussalam. The research was qualitative using non-doctrinal juridical or sociological methods to reform the legal order of polygamy in Raqan using studies of legal order theory, al-hudud (legal boundaries), and al-maslahah, using a historical approach and a legal philosophy approach. The findings showed that the idea of ​​a legal order for polygamy in the family law community in Nanggroe Aceh Darussalam is the implementation of the idea of ​​legal governance between compliance with Sharia and state law perfectly through Raqan renewal. Legal reform is an illustration and parameter in implementing polygamy to realize benefits for individuals and society. And, protect the position of women and children who have not been accommodated in marriage law, so that they can live a harmonious life.